2005
DOI: 10.1002/ajh.20261
|View full text |Cite
|
Sign up to set email alerts
|

X-linked lymphoproliferative syndrome presenting with systemic lymphocytic vasculitis

Abstract: X-linked lymphoproliferative syndrome (XLP) is a rare, often fatal, primary immunodeficiency disease characterized by an abnormal response to Epstein-Barr virus (EBV) infection. The gene responsible for XLP has been identified as SH2D1A/DSHP/SLAMassociated protein (SAP). The major clinical manifestations include fulminant infectious mononucleosis, lymphoproliferative disorder, and dysgammaglobulinemia. Affected males uncommonly present with lymphocytic vasculitis in addition to aplastic anemia. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 16 publications
1
25
0
3
Order By: Relevance
“…8 Previous studies have shown that SH2D1A protein expression is undetectable in patients with confirmed XLP. 9,18 The diagnosis of XLP is difficult given its clinical heterogeneity and the lack of a rapid diagnostic laboratory test, particularly with males manifesting a phenotype consistent with XLP but without a family history. Recent improvement of the prognosis of XLP by transplantation of hematopoietic stem cells makes early diagnosis more important.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have shown that SH2D1A protein expression is undetectable in patients with confirmed XLP. 9,18 The diagnosis of XLP is difficult given its clinical heterogeneity and the lack of a rapid diagnostic laboratory test, particularly with males manifesting a phenotype consistent with XLP but without a family history. Recent improvement of the prognosis of XLP by transplantation of hematopoietic stem cells makes early diagnosis more important.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for developing multiple autoimmune as well as infiltrative lymphoproliferative disorders involving different organ systems, such as uveitis, hepatitis, glomerulonephritis, infiltrative pulmonary lesions, and encephalitis and myelitis (manifesting as aseptic meningitis) in some patients with ALPS is being recognized on their long-term follow-up over many years (Table 1). [15][16][17][18][19] The most common laboratory findings include the presence of cytopenias secondary to autoimmune destruction or splenic sequestration and polyclonal hypergammaglobulinemia. Anemia is nearly universal because of a combination of factors, including hypersplenism, autoimmunity, and iron deficiency.…”
Section: Clinical and Laboratory Featuresmentioning
confidence: 99%
“…The word syndrome refers to the many common symptoms shared by ALPS patients. The word lymphoproliferative describes the unusually large numbers of white blood cells (called lymphocytes) stored in the lymph nodes and spleens of people with ALPS (8).…”
Section: Introductionmentioning
confidence: 99%